Emergence of “neokruzhnichesky” discord in old believers’ Belokrinitskaya hierarchy in 1862 - Marina Voloskova (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
At present, the history of the emergence of the «neocircular discord» of the Belokrinitsky hierarchy is poorly studied. Even in the memory of the Old Believers themselves, information about the once former division of the Old Believers who accept the Belokrinitsky hierarchy into the so-called circle and neokruzhniki is scattered. There is very little system information about events that relate to the «neocircular discord». There are also few scientific studies devoted to the events related to the «District Message» of 1862, and the available ones are devoted to individual episodes and names. Insufficient knowledge of this topic leads to inaccuracies in studies devoted to spiritual and social thought of the late XIX-early XX century, leaves blank spots in the history of Old Believers, leads to historiographical errors in the interpretation of certain phenomena. The article examines the history of the emergence of the «neocircular discord» of the Belokrinitsky hierarchy in 1862. The publication of the «District Message» provoked discord in the Old Believer Church of the Belokrinitsky hierarchy. The search for compromises and further attempts at reconciliation in the late XIX – early XX century did not bring the proper result. In addition, the neocircular discord marked the beginning of a theological discussion on a number of issues in relation to the state and the dominant Church. In particular, the most discussed issue was the possibility of commemoration at the Liturgy of the tsar. In addition, the publication of the «District Epistle» influenced the transition to the co-faith of a number of clergy of the Belokrinitsa hierarchy, which in turn had serious consequences for historical science, since in the process of cooperation with the historian of the church, Doctor of theology I. N. Subbotin, Archdeacon Filaret gave him the archive of the Belokrinitsa metropolis, the materials of which were subsequently published.